PROSPECTS FOR DEVELOPMENT OF COMPOSITE STRUCTURES BASED ON CARBON-CARBON MATERIAL AND TITANIUM ALLOY - Antsiferov, V.N.; Astashina, N.B.; Smetkin, A.A.; Kachenyuk, M.N.; Strukov, N.N. (Perm Federal Research Centre Journal, 2015)
The paper presents the results of the research aimed at the formation and study of basic properties of composite structures made on the basis of carbon - carbon material and titanium alloy. At the present stage of development of fundamental and applied research there exist opportunities to create fundamentally new compositions with desired properties, performed on the basis of dissimilar materials. Studies have shown that the use of the technology of surfacing and spraying ensures the formation of high-grade titanium coating of the carbon material with adhesive strength of3.5-5.0 MPa and the ability to control the structure of the coating. The direct dependence of the bond strength of UKM - titanium post on the sintering temperature has been identified. At 1100 ºC the strength is minimal, with increasing temperature there is an increase in strength. The maximum bond strength of the design "titanium composite" connection was 9.2 MPa. The influence of cyclic loading on the bond strength UKM - titanium post has been identified. When the number of cycles is up to1000, a significant reduction of strength does not occur. With an increase in the number of cycles to 10 000 the strength is reduced to 7.3 MPa.